Monetary policy and systemic risk-taking in the Euro area investment fund industry: A structural factor-augmented vector autoregression analysis - Jin, Xisong; Nadal De Simone, Francisco (Journal of Financial Stability, 2020)
Abundant references to threats to financial stability likely posed by systemic risk-taking in the euro area investment fund industry in an era of persistent low interest rates have not been accompanied by robust supportive empirical evidence. This is the first study that assesses the effects of euro area conventional and unconventional monetary policy shocks on coherent systemic risk measures applied to the investment fund industry. This research finds evidence of systemic risk-taking notably in the forms of contagion and increased vulnerability. It seems more material following conventional than unconventional monetary policy shocks. There is heterogeneity in the results, as the investment focus is important for assessing investment funds’ contribution to systemic risk. Fund types most affected by significant systemic risk-taking are bond funds, mixed funds and real estate funds. Some evidence of heightened vulnerability in equity funds is also present. Increase in leverage is part of the risk-taking mechanism. A key policy implication is that persistently accommodative monetary policy geared toward preserving price stability may face an intertemporal trade-off with financial stability, making it necessary to coordinate monetary and macroprudential policies.